Clinical Outcomes of Double-row Fixation in Chronic Lateral Ankle Instability—Functional Success with Persistent Mechanical Laxity: A Retrospective Study - Jin Su Kim; Ken Meng Tai; Sang Bum Kim (Journal of Foot and Ankle Surgery (Asia Pacific))
Introduction: Chronic lateral ankle instability (CLAI) is a common consequence of recurrent ankle sprains, often requiring surgical treatment. This study aims to evaluate the clinical and radiological outcomes of a double-row fixation technique for the anterior talofibular ligament (ATFL) and knotless suture anchors for the calcaneofibular ligament (CFL) in CLAI patients. Additionally, the study examines the CFL tortuosity angle as a diagnostic and outcome measurement tool through magnetic resonance imaging (MRI). Materials and methods: This retrospective study included 60 patients who underwent surgery for CLAI between March 2020 and February 2021. The surgical procedure involved a double-row fixation for ATFL repair and knotless suture anchors for CFL reinforcement. Clinical outcomes were assessed using the Cumberland Ankle Instability Tool (CAIT), manual anterior drawer test (ADT), talar tilt (TT), and stress radiographs. The CFL angle was measured on MRI scans pre- and postoperatively to assess ligament integrity. Statistical analysis was conducted using paired t-tests, Pearson correlation, and logistic regression to evaluate changes in clinical and radiological parameters. Results: Postoperative outcomes showed significant improvement across all parameters. The average CAIT score increased from 9.5 preoperatively to 24.8 postoperatively (p < 0.001), indicating substantial functional improvement. Radiological measures of anterior translation decreased from 8.7 to 6.47 mm (p < 0.001), and TT angle improved from 8.6° to 6.0° (p < 0.001). The CFL tortuosity angle decreased from an average of 63.1° preoperatively to 25.9° postoperatively (p < 0.001), suggesting restored ligament integrity. Despite these improvements, 42.6% of patients exhibited residual mechanical laxity on physical examination, with 22 patients exhibiting grade I and 4 patients with grade II laxity on anterior drawer, and 19 patients with grade I and 4 with grade II laxity on TT. Conclusion: The double-row fixation technique for ATFL and CFL provides significant clinical and radiological improvements. However, a notable percentage of patients continue to demonstrate residual mechanical instability postoperatively. Future research should explore strategies to address residual mechanical laxity to optimize patient recovery and long-term prognosis. Level of evidence: Level III, retrospective cohort study.